PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PROJECT BASED LEARNING PADA MATERI TITRASI KOMPLEKSOMETRI - Samosir, Rafidah Almira; Ardila, Mutia (Lantanida Journal, 2025)
Research on developing project-based learning materials for complexometric titration materials is still rare, despite the fact that these materials have shown promising in chemical education. The objective of this project is to create a complexometric titration learning resource based on Project-Based Learning (PjBL) and assess its viability and efficacy in improving students' psychomotor abilities and learning outcomes. Using the ADDIE paradigm, the study used a Research and Development (R&D) methodology. The media, which includes instructive videos, digital resources, and a useful mini-project, was created with Adobe Flash CS6. 42 chemical education students from Universitas Negeri Medan (UNIMED) participated in a restricted trial after validation by two subject matter experts and two media experts. Subject matter experts and media experts gave the validation results an average score of 3.29 and 3.46, respectively, which both fell into the "highly feasible" category. During the implementation phase, the experimental class outperformed the control group in terms of learning outcomes (gain score of 0.722) and psychomotor skills (average score of 3.64). With an average score of 3.46, students' reactions to the media were likewise very favorable. These results demonstrate that the developed media is useful for enhancing students' engagement in learning complexometric titration, conceptual knowledge, and laboratory skills.